(untitled) (Global Journal of Human-Social Science, 2023)
We intend to discuss the heteroidentification committees in competition for racial quotas for black people to ingress in a public university in Brazilian Higher Education Firstly we begin with a brief presentation of this educational system and the context of the affirmative action policy in racial markers in Brazil Secondly we introduce the conceptual differentiation between self-identification of the dimension of to be and self-declaration of the dimension of to do Thirdly we present Brazil s socio-legal context of racial affirmative action policies Finally we argue that the result of heteroidentification committees does not invalidate racial selfidentifications but only self-declarations That procedure is an essential method of social control of the public policy of racial affirmative actions in Brazilian Higher Education